Enhanced thermoelectric performance of skutterudite Co1−yNiySn1.5Te1.5−x with switchable conduction behavior. (November 2022) - Meledath Valiyaveettil, Suneesh; Qorbani, Mohammad; Hsing, Cheng-Rong; Chou, Ta-Lei; Paradis-Fortin, Laura; Sabbah, Amr; Srivastava, Divya; Nguyen, Duc-Long; Ho, Thi-Thong; Billo, Tadesse; Ganesan, Peramaiyan; Wei, Ching-Ming; et al.
Abstract: A fine control of carriers in solids is the most essential thing while exploring any functionality. For a ternary skutterudite like CoSn1·5 Te1.5− x, which has been recently recognized as a potential material for thermoelectric conversion, the dominant carrier could be either electrons or holes via chemically tuning the quaternary Sn2 Te2 rings in the structure. Both theoretical calculation and different spectroscopic probes, such as X-ray photoelectron spectroscopy (XPS) and X-ray absorption spectroscopy (XAS) were employed to unveil the conduction type switching details. On the other hand, a Ni-for-Co substitution was applied to enhance electronic transport, and thereby the thermoelectric power factor. Thanks to the substantial cut-off of lattice thermal conductivity by the characteristic Sn2 Te2 rings in the skutterudite structure, ultimately a 70-fold increase in the dimensionless figure-of-merit (zT) is achieved at 723 K with the nominal composition Co0·95 Ni0·05 Sn1·5 Te1.5. Graphical abstract: Image 1 Highlights: Conduction type switching from n -to p -type in ternary CoSn1. 5 Te1.5− x skutterudite by fine tuning the X4 rings. Observation of a reduced electron transfer from Te to Co site in Sn-rich condition. Optimization of electronic transport by Ni substitution toward improving n -type power factor. About 70 times enhancement in the thermoelectric figure-of-merit ( z T ), reaching 0.73 at 723 K.